Ruthenium nanoparticles supported on carbon-based nanoallotropes as co-catalyst to enhance the photocatalytic hydrogen evolution activity of carbon nitride. (May 2021) - Álvarez-Prada, Ignacio; Peral, Daniel; Song, Mary; Muñoz, Jose; Romero, Nuria; Escriche, Lluís; Acharjya, Amitava; Thomas, Arne; Schomäcker, Reinhard; Schwarze, Michael; Sala, Xavier; Tasbihi, Minoo; et al.
Abstract: Development of competent and cost-effective materials for hydrogen evolution reaction (HER) has been attracting great attention since hydrogen is hailed as a promising environmentally friendly energy source to reduce the greenhouse emissions. Herein, Ru(0) nanoparticles (RuNPs) have been stabilized onto the surface of four different conducting carbon nanomaterials (CNMs) from 0D to 3D, such as 0D carbon nanohorns (CNH), 1D single-walled carbon nanotubes (CNTs), 2D reduced graphene oxide (rGO) and 3D graphite (GP), for their use in the photocatalytic HER. For this aim, the resulting RuNP@CNMs where physically mixed with mesoporous graphitic carbon nitride (mpg-CN) in an optimum composition ratio to maximize the photocatalytic HER activity. Notably, the resulting four hybrid RuNPs@CNM/mpg-CN materials showed an outstanding increase in the hydrogen evolution reaction (HER) when compared with the pristine mesoporous graphitic carbon nitride without co-catalyst. A comparison on the photocatalytic activity of the four hybrid RuNPs@CNMs physically mixed with mpg-CN and a deep study on the fate of the nanohybrids after catalysis are presented. Graphical abstract: Image 1 Highlights: Photocatalytic hydrogen evolution reaction using sunlight as renewable energy source. Study of the hydrogen evolution reaction activity of carbon nitride and ruthenium nanoparticles. Performance of the photocatalytic reaction with variable concentration of ruthenium nanoparticles.